Digital Finance Usage and Its Impact on Consumer Economic Behavior Based on National Data - Umamah Mumtazah Askhiyah (Journal of Applied Econometric, 2026)
Background:The rapid proliferation of digital financial technologies has dramatically transformed consumer engagement with financial services. However, the comprehensive impact of digital finance on economic behavior remains inadequately understood. The shift toward digital finance is reshaping how households interact with financial services, but its full effects on consumer economic behavior are yet to be explored.Objective:This study aims to examine the causal and correlational relationships between the intensity of digital finance usage and multiple dimensions of consumer economic behavior, using nationally representative household survey data.Method:The research employs propensity score matching, instrumental variable estimation, and panel data methods to analyze the data. These techniques allow for a thorough understanding of the impact of digital finance adoption on household consumption, savings, financial literacy, and other economic behaviors.Findings and Implications:The study finds that digital finance adoption increases household consumption expenditure by 8.7%, yet paradoxically reduces savings balances by 5.8%, despite improving formal financial inclusion. Digital finance users show significantly enhanced financial literacy, planning behavior, and management practices, with financial literacy scores rising by 1.4 points after adoption. However, vulnerable populations, particularly young lower-middle-income households, experience higher debt-to-income ratios and more frequent payment difficulties.Conclusion:The research highlights the importance of digital finance in improving financial inclusion and consumer economic behavior, yet it also emphasizes the need for targeted regulatory approaches. Policymakers should focus on promoting digital finance while ensuring safeguards for vulnerable populations to mitigate the associated risks, such as increased debt levels and payment difficulties.